PENGUATAN UMKM SIAP EKSPOR DI PROVINSI KEPULAUAN BANGKA BELITUNG - Reniati Reniati; Nizwan Zukhri; Hamsani Hamsani; Darus Altin (Universitas Mataram, 2023)
The government is targeting the contribution of Micro, Small and Medium Enterprises (MSME) products to export commodities to reach 21.6 percent by 2024. The solutions and achievement targets to be achieved in this activity are first, observations are made on 11 MSMEs that are ready to export. Second, provide training related to increasing MSME export competency and third, provide the opportunity to take part in Export Assessments. The Export Ready MSME Strengthening Program is carried out in collaboration with the Bangka Belitung Islands Province Cooperative and MSME Service. This aim is to provide information to MSMEs about existing export opportunities, to improve participants' English language skills, to introduce digital technology, especially in digital marketing and the use of advertising videos. After the activities are carried out, training participants are expected to have better English language skills and be able to communicate confidently in an international business environment. By applying digital technology and digital marketing, it is hoped that MSMEs can expand market reach and increase product promotion through attractive advertising videos. The ability to utilize artificial intelligence technology in copywriting is also expected to provide a competitive advantage for MSMEs in creating more persuasive and interesting marketing content. This training will encourage MSMEs to prepare comprehensive business proposals and successfully obtain financial support to develop their business. By achieving these results, it is hoped that MSMEs in the Bangka Belitung Islands can be upgraded to become quality, resilient, export-oriented businesses and make a sustainable contribution to the local economy and community welfare. By holding MSME Week 2023 which focuses on the theme